Personal Data Protection in Private Sector Electronic Systems for Businesses: Indonesia vs. South Korea - Ninne Zahara Silviani; Rina Shahriyani Shahrullah; Vanessa Riarta Atmaja; Park Ji Hyun (Jurnal Hukum dan Peradilan, 2023)
This paper explores the various practices surrounding the legal framework for protecting personal data in the context of private electronic systems used by commercial companies. The research's main focus is the ambiguity of the goals of Indonesia's Electronic System providers and how they may adopt better practices to enhance data protection within Electronic System Providers, so this extensive examination also includes a thorough comparison of the personal data protection laws in South Korea and Indonesia. This investigation aims to carefully define, evaluate, and harmonize the two countries' unique legal systems. This study uses a normative legal research framework with a Teleological and Legal Protection approach as its research technique. Additionally, it uses the comparative law method to clarify, outline, and examine the specifics of the personal data protection laws that are now in force in Indonesia and South Korea. The results of this research go beyond identifying problems; they are expected to produce a thorough understanding of the complexities surrounding personal data security in the context of electronic commerce. These discoveries are well-positioned to be the foundation for upcoming regulatory improvements, eventually encouraging more potent and reliable data protection procedures in both nations.